Pengembangan Game Edukasi Pengenalan Makanan Sehat Menggunakan Kinect - Iqbal Firmansyah; Muhammad Aminul Akbar; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Healthy food are food that hygienic and contain balanced nutrients needed by the body. In 2013 the national malnutrition rate in children aged 5-12 years is still high, that is the prevalence of lean 11.2 percent, the short prevalence 30.7 percent, and the prevalence of obese 18.8 percent. It's necessary for introduction of healthy foods as a step to reduce malnutrition level. Introduction method can be done with learning through educational games, so that the learning process is more fun and get more effective results. The game will be titled